2017
DOI: 10.3389/fphar.2017.00630
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferia parviflora Extract Exhibits Anti-cancer Activity against HeLa Cervical Cancer Cells

Abstract: Kaempferia parviflora (KP) has been traditionally used as a folk remedy to treat several diseases including cancer, and several studies have reported cytotoxic activities of extracts of KP against a number of different cancer cell lines. However, many aspects of the molecular mechanism of action of KP remain unclear. In particular, the ability of KP to regulate cancer cell growth and survival signaling is still largely unexplored. The current study aimed to investigate the effects of KP on cell viability, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…The ability of KP extract in suppressing the activity of MMPs was independent on the presence of EGF, since KP extract could be able to strongly overcome the effects of EGF. Our findings are in line with our previous studies showing that KP suppressed MMP-2 production in cervical cancer, HeLa cells [ 10 ]. Similar observation was reported in colorectal carcinoma cells, where a flavonoid, myricetin, inhibited MMP-2 activity and cell invasion [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The ability of KP extract in suppressing the activity of MMPs was independent on the presence of EGF, since KP extract could be able to strongly overcome the effects of EGF. Our findings are in line with our previous studies showing that KP suppressed MMP-2 production in cervical cancer, HeLa cells [ 10 ]. Similar observation was reported in colorectal carcinoma cells, where a flavonoid, myricetin, inhibited MMP-2 activity and cell invasion [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…We first performed cell viability assay to evaluate the cytotoxicity of KP extract in SKOV3 cells. It was found that KP extract decreased cell viability of ovarian cancer in a concentration-dependent manner with IC50 of approximately 0.5 mg/mL, which was slightly higher than the previously reported IC50 of KP in cervical cancer cell line, HeLa [ 10 ]. Interestingly, KP extract also strongly exhibited the reduction of ovarian cancer cell viability in the presence of EGF, suggesting that KP has potent cytotoxic effects, which overcome the influence of EGF in maintaining cell viability.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Medicinal plants are good sources of potential active anti-inflammatory agents. We previously reported various pharmacological effects of certain plants which have been traditionally used in Thailand to treat different diseases, and many parts of their mechanisms of action were associated with the modulation of inflammatory signal transduction pathways [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, 25 methoxyflavones and their glycosides were identified and quantified as predominant flavonoids from rhizome extracts (Supplementary Table 2) [23][24][25][26]. The presence of these compounds contributed to a wider range of medicinal effects such as antiinflammatory [27], antioxidant [28,29], antiproliferative activity [30], hepatoprotective effect [31], and anticancer [32].…”
Section: Introductionmentioning
confidence: 99%